2018
DOI: 10.1111/cas.13708
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic analysis of eribulin safety in breast cancer patients using real‐world postmarketing surveillance data

Abstract: Postmarketing surveillance is useful to collect safety data in real‐world clinical settings. In this study, we applied postmarketing real‐world data on a mechanistic model analysis for neutropenic profiles of eribulin in patients with recurrent or metastatic breast cancer. Demographic and safety data were collected using an active surveillance method from eribulin‐treated recurrent or metastatic breast cancer patients. Changes in neutrophil counts over time were analyzed using a mechanistic pharmacodynamic mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Therefore, the aforementioned factor is unlikely to cause neutropenia, suggesting the potential existence of other causal factors. Since the mechanism underlying neutrophil reduction due to pre‐treatment ALB levels was not previously reported, 18 a more detailed future study is required. Nonetheless, since our study indicates that the risk of severe neutropenia may be increased owing to a reduction in renal function in Japanese patients, neutropenia may result from a reduction in eribulin CL owing to decreased renal function.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, the aforementioned factor is unlikely to cause neutropenia, suggesting the potential existence of other causal factors. Since the mechanism underlying neutrophil reduction due to pre‐treatment ALB levels was not previously reported, 18 a more detailed future study is required. Nonetheless, since our study indicates that the risk of severe neutropenia may be increased owing to a reduction in renal function in Japanese patients, neutropenia may result from a reduction in eribulin CL owing to decreased renal function.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study 17 reported that decreased ALB levels owing to pre‐treatment may be associated with severe neutropenia, thus affecting the time course of neutrophil reduction 21 . Furthermore, Kawamura et al 18 reported that the severity of neutropenia varies depending on the neutrophil count and ALB levels at the initiation of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report by the US Food and Drug Administration, experts are considering to adapt real‐world evidence for complementing the knowledge gained from traditional clinical trials (in which limitations render generalization to clinical practice difficult) 24 . A prominent example is the PMS data safety management analysis performed by Kawamura et al 25 By using a mechanistic PD model of eribulin‐induced neutropenia, Kawamura et al gained insight into the importance of treatment regimen selection. Our results reflect a real‐world setting, in which follow‐up intervals, dosing schedules, and preventive safety measures are tailored to each patient.…”
Section: Discussionmentioning
confidence: 99%
“…4 Based on the mechanisms underlying chemotherapy-induced immunomodulation, 29 eribulin is a candidate chemotherapeutic agent in combination therapy for TNBC with antagonists of immune checkpoint signaling because it does not always require steroids and is a well-tolerated drug, which is particularly suitable for TNBC. 8,30 Epithelial-mesenchymal transition is a key process in cancer metastasis. It has been shown to contribute to immunosuppression in breast cancer.…”
Section: Discussionmentioning
confidence: 99%